2020
DOI: 10.22541/au.160315276.60907051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary acid load and risk of prostate cancer: (a case-control study)

Abstract: Background: There are few studies which have shown inconsistent results regarding the associations between dietary acid load (DAL) and the risk of cancer. This study aimed to examine the association between DAL and prostate cancer (PC) risk among Iranian population. Methods: One hundred and twenty participants (60 controls and 60 newly diagnosed PC patients) engaged in a hospital-based case-control study. Validated 160-items semi-quantitative food frequency questionnaire (FFQ) was used to assess usual dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Two studies were also removed during the second screening phase because these studies were conference. Finally, three cohorts ( 21 , 24 , 30 ) and seven case-control studies ( 19 , 20 , 22 , 23 , 31 33 ) were comprised in the current systematic review and meta-analysis. Figure 1 shows the flow diagram of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were also removed during the second screening phase because these studies were conference. Finally, three cohorts ( 21 , 24 , 30 ) and seven case-control studies ( 19 , 20 , 22 , 23 , 31 33 ) were comprised in the current systematic review and meta-analysis. Figure 1 shows the flow diagram of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up period in cohort studies ranged from 7.3 to 8 years. The type of studied cancers were breast ( 21 , 30 , 32 , 33 ), colorectal ( 19 , 22 ), prostate ( 20 ), lung ( 23 ), pancreas ( 24 ), and glioma ( 31 ). Most of the studies ( n = 9) used the food frequency questionnaire (FFQ) tool for assessment of the food intake.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (Park et al , 2019; Mehranfar et al , 2020; Nasab et al ., 2021; Ronco et al , 2020; Safabakhsh et al , 2020; Ronco et al, 2021a,b; Shi et al , 2021) reported diet acidity load as PRAL, seven (Park et al , 2019; Mehranfar et al , 2020; Ronco et al , 2020; Safabakhsh et al , 2020; Ronco et al, 2021a,b; Shi et al , 2021) as NEAP, two as NAE (Wright et al , 2005; Park et al , 2019) and one as A:P (Park et al , 2019). All studies used a food frequency questionnaire for dietary assessment.…”
Section: Resultsmentioning
confidence: 99%
“…All studies used a food frequency questionnaire for dietary assessment. From the included studies, three explored the risk of cancer across the tertiles of dietary acid load scores (Mehranfar et al , 2020; Nasab et al ., 2021; Safabakhsh et al , 2020), five across quartiles (Park et al , 2019; Ronco et al , 2020; Ronco et al, 2021a,b; Shi et al , 2021) and one across quintile (Wright et al , 2005). Incidents in the lowest category of dietary acid load were considered as a reference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation